2013
DOI: 10.1021/am4017347
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Sensing Performance of Electrospun Pt-Functionalized NiO Nanotubes with Chemical and Electronic Sensitization

Abstract: Pt-functionalized NiO composite nanotubes were synthesized by a simple electrospinning method, and their morphology, chemistry, and crystal structure have been characterized at the nanoscale. It was found that the Pt nanoparticles were dispersed uniformly in the NiO nanotubes, and the Pt-functionalized NiO composite nanotubes showed some dendritic structure in the body of nanotubes just like thorns growing in the nanotubes. Compared with the pristine NiO nanotube based gas sensor and other NiO-based gas sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(76 citation statements)
references
References 23 publications
0
76
0
Order By: Relevance
“…[3][4][5][6]. Following previous literatures, adding other metal oxides and dopants plays an important for promoting the specific gas sensing reaction by the spilled over effect [7,8].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6]. Following previous literatures, adding other metal oxides and dopants plays an important for promoting the specific gas sensing reaction by the spilled over effect [7,8].…”
Section: Introductionmentioning
confidence: 94%
“…Dodd first presented a report on a sensor array in 1982 [7]. After that, many research teams conducted studies on sensor arrays for the detection of gases in various fields such as environmental monitoring, food and beverage analysis, and disease diagnosis [8][9][10]. However, it is difficult to reduce the distance between the sensing layers of a sensor array because the metal oxides have different operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It is well reported that, there are two kinds of sensitization mechanisms for noble metals as catalysts, electronic and chemical mechanisms (see Fig. 11) [16,71,72]. The modification of the surface properties by decorating with Pt metal may causes different electrical characteristics due to the variation in the depletion layer width.…”
Section: Hydrogen Sensing Performance Of Pt-decorated Gan Nws Sensormentioning
confidence: 99%
“…Among them, 1-dimensional materials such as nanowires or nanotubes have been actively researched as sensor materials due to their linear structured advantage of being easily applicable as an electrical channel in the system [10,11]. In particular, nanotubes seem to show better sensing performance compared to nanowires due to their higher surface area [11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nanotubes seem to show better sensing performance compared to nanowires due to their higher surface area [11].…”
Section: Introductionmentioning
confidence: 99%